SUBSTITUSI TEPUNG TERIGU DENGAN TEPUNG BIJI DURIAN PADA BISKUIT SEBAGAI MAKANAN TAMBAHAN BALITA UNDERWEIGHT[Substitution of Wheat Flour with Durian Seed Flour in Biscuits as a Food Supplement of Under Five Children with Underweight] - Besti Verawati; Nopri Yanto (Universitas Airlangga, 2019)
Durian seed flour content high protein, therefore it is potential to become food supplement (such as biscuits) for under five children. The purpose of this research was to formulate biscuit with durian seed flour as food supplement for underweight children under five in Kampar District, Riau. This was experimental research with Completely Randomized Design (CRD). The substitution of durian seed flour treatment was F1=15%, F2=20% dan F3=25%. ANOVA was used to analyzed the difference between groups and Duncan test for within groups. Semi-trained panelists consist of 25 undergraduate nutrition student of Universitas Pahlawan Tuanku Tambusai. There was no difference in flavor, color, and aroma of biscuit subsitute with durian seed flour. However, there was a difference in texture (p=0.000). Duncan test showed that F2 have a better acceptance level compared to F1 dan F3. Proksimat analysis for selected formula revealed that biscuit F2 contain 6.72% water, 1.36% ash, 5.57% protein, 13.75% fat, and 72.60% carbohydrate. Energy and protein content of F2 were 218 kcal and 2.7 grams per serving size (4 biscuits= 50 gram) and have met the 20% requirement of underweight children. Substitution of wheat flour with 25% durian seed flour has a similar organoleptic characteristics (flavor, color, and aroma) with wheat flour biscuits. Therefore, it can be a supplemetary food for underweight children. It is necessary to add other food ingredients to improve the texture and increasing the protein content in accordance with SNI.